2016
DOI: 10.1093/rheumatology/kew400
|View full text |Cite
|
Sign up to set email alerts
|

Modelling clinical systemic lupus erythematosus: similarities, differences and success stories

Abstract: Mouse models of SLE have been indispensable tools to study disease pathogenesis, to identify genetic susceptibility loci and targets for drug development, and for preclinical testing of novel therapeutics. Recent insights into immunological mechanisms of disease progression have boosted a revival in SLE drug development. Despite promising results in mouse studies, many novel drugs have failed to meet clinical end points. This is probably because of the complexity of the disease, which is driven by polygenic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 156 publications
(184 reference statements)
1
40
0
Order By: Relevance
“…Second, we investigated a possible correlation between TCRβ+CD138+ cells and the progression of disease in MRL/Lpr mice and found that the frequency of TCRβ+CD138+ cells progressively increased with the age of mice (Figure 1B). Moreover, the increase in TCRβ+CD138+ cell population was also detected in pristine-injected Balb/c and C57BL/6 mice (Supplemental Figure 1C and D), which also develop lupus-like autoimmune symptoms [27]. It is important to note that in B6/lpr mice, TCRβ+CD138+ cells were previously reported to be confined to the lymph nodes [25], however, we found high percentage of these cells also in the thymus, spleen, lymph nodes and blood of MRL/Lpr mice (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Second, we investigated a possible correlation between TCRβ+CD138+ cells and the progression of disease in MRL/Lpr mice and found that the frequency of TCRβ+CD138+ cells progressively increased with the age of mice (Figure 1B). Moreover, the increase in TCRβ+CD138+ cell population was also detected in pristine-injected Balb/c and C57BL/6 mice (Supplemental Figure 1C and D), which also develop lupus-like autoimmune symptoms [27]. It is important to note that in B6/lpr mice, TCRβ+CD138+ cells were previously reported to be confined to the lymph nodes [25], however, we found high percentage of these cells also in the thymus, spleen, lymph nodes and blood of MRL/Lpr mice (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Generation of Snerv1/Snerv2-competent NZB and NZW will permit targeted approaches to manipulate the gp70 phenotype in vivo and can be used to conclusively test the requirement for dysregulated NEERV in the pathogenesis of lupus. Although Snerv1 and Snerv2 are in epistasis with additional susceptibility loci that enhance disease in models of spontaneous lupus (Celhar and Fairhurst, 2017;Crampton et al, 2014;Morel, 2010), such experiments will elucidate the connection between ERV mis-regulation and lupus pathogenesis. Using Snerv1/Snerv2-competent lupus-prone mice, it will be possible to rigorously test how tolerance is lost in the setting of high NEERV autoantigen production, how anti-NEERV autoantibodies are induced, and how NEERV dysregulation itself contributes to lupus severity.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of Snerv1/2-competent NZB and NZW will permit targeted approaches to manipulate the gp70 phenotype in vivo, and can be used to conclusively test the requirement for dysregulated NEERV in the pathogenesis of lupus. While Snerv1 and Snerv2 are in epistasis with additional susceptibility loci that enhance disease in models of spontaneous lupus (Celhar and Fairhurst, 2017;Crampton et al, 2014;Morel, 2010), such experiments will elucidate the connection between ERV misregulation and lupus pathogenesis. Using Snerv1/2-competent lupus-prone mice, it will be possible to rigorously test how tolerance is lost in the setting of high NEERV autoantigen production, how anti-NEERV autoantibodies are induced, and how NEERV dysregulation itself contributes to lupus severity.…”
Section: Discussionmentioning
confidence: 99%
“…NZB-and NZW-based lupus models are widely used in pre-clinical drug efficacy trials, as they recapitulate more clinical features of human SLE than other mouse strains (Celhar and Fairhurst, 2017;Li et al, 2017). Of the few drugs approved for treatment of SLE by the FDA, essentially all-systemic immunosuppressants, antimalarials, anti-BAFF, anti-CD20, anti-CTLA-4, interferon-alpha blockade, and toll-like receptor agonists-were tested pre-clinically in NZB/W models (Celhar and Fairhurst, 2017). Clarifying the role of NEERV in disease progression will shape how pre-clinical testing for lupus nephritis proceeds and whether it may be feasible to pursue the development of therapeutics that target ERV.…”
Section: Discussionmentioning
confidence: 99%